18 Developing a wire-injury model of calcific aortic stenosis. (17th July 2020) - Woodward, Holly; Thomson, Adrian; Macrae, Vicky; Hadoke, Patrick
Abstract : Calcific aortic stenosis (CAS) is the most common valve disease in the Western world and has no effective pharmaceutical treatment options. Stenosis can be caused by a combination of mechanical injury, inflammation, fibrosis and calcification, which eventually leads to left ventricular hypertrophy and heart failure. Males are at greater risk of developing aortic calcification and androgens are a risk factor in this condition. Elucidating the mechanisms underlying male predisposition to aortic stenosis is hampered by the lack of appropriate animal models; particularly valve-injury models which develop stenosis and calcification. This study describes introduction of a murine model for investigation of CAS in male and female mice. Damage was induced in the aortic valve of adult, male and female C57BL/6J mice by inserting a guidewire into the left ventricle under ultrasound guidance and rubbing the valve by rotating the guidewire twenty times. Pilot investigations demonstrated low mortality and weight loss (less than 15% of pre-surgery weight) but no significant changes in aortic or cardiac function (measured by ultrasound) following surgery. H&E staining demonstrated variable thickening of valve cusps (30-140 μM). Cusps displayed fibrosis and stained positive for inflammatory cells (Mac2). No calcification (as determined by alizarin red staining) was observed. These results suggest that wire injury is producing mild damage and non-calcific remodelling in the aortic valve, indicating that greater damage is required to produce haemodynamic changes and aortic stenosis with calcification. Successful development of this model will provide a valuable tool for clarifying the mechanisms that predispose males to CAS. Conflict of Interest: none